Electrical impedance myography in individuals with collagen 6 and laminin α‐2 congenital muscular dystrophy: a cross‐sectional and 2‐year analysis. Issue 1 (25th April 2017) - Nichols, Carmel; Jain, Minal S.; Meilleur, Katherine G.; Wu, Tianxia; Collins, James; Waite, Melissa R.; Dastgir, Jahannaz; Salman, Anam; Donkervoort, Sandra; Duong, Tina; Keller, Katherine; Leach, Meganne E.; et al.
ABSTRACT: Introduction: Electrical impedance myography (EIM) is a noninvasive electrophysiological technique that characterizes muscle properties through bioimpedance. We compared EIM measurements to function, strength, and disease severity in a population with congenital muscular dystrophy (CMD). Methods: Forty‐one patients with CMD, either collagen 6 related disorders (COL6‐RD; n = 21) or laminin α‐2‐related disorders (LAMA2‐RD; n = 20), and 21 healthy pediatric controls underwent 2 yearly EIM exams. In the CMD cohorts, EIM was compared with functional and strength measurements. Results: Both CMD cohorts exhibited change over time and had correlation with disease severity. The 50‐kHZ phase correlated well with function and strength in the COL6‐RD cohort but not in the LAMA2‐RD cohort. Discussion: EIM is a potentially useful measure in clinical studies with CMD because of its sensitivity to change over a 1‐year period and correlation with disease severity. For COL6‐RD, there were also functional and strength correlations. Muscle Nerve 57 : 54–60, 2018